Penggunaan Adjektiva dalam Biografi Gusti Noeroel dan Relevansinya Terhadap Nilai-Nilai Karakter yang Dikembangkan di Sekolah - Putri, Meilyana Puspasari; , Drs. Agus Budi Wahyudi, M.Hum (2016)
The aims of this research are to describe the adjectives found in Gusti Noeroel: Streven Naar Geluk (Persuit of Happiness) biography by Ully Hermono, to describe the characters of Gusti Noeroel in form of adjectives presented in sentences and to describe the characters Gusti Noeroel of which relevant with school value. This study was descriptive qualitative research the source of the data in this research was Gusti Noeroel: Streven Naar Geluk (Mengejar Kebahagiaan) biography written by Ully Hermono. The way to collect the data in were notes and document. The technique of analyzing the data in this research was agih method with teknik ganti and padan method. The technique of validation used in this research is trianggulation technique. The result of the study are 1) the are 3 kinds of adjectives found in Gusti Noeroel: Streven Naar Geluk (Persuit of Happiness) biography by Ully Hermono: adjectiva dasar, adjectiva turunan, and adjectiva majemuk, 2) there are 14 characters of Gusti Noroel in the form of adjective such as brave,calm, smart, simple and confident. And there are 14 characters in adjectives which relevant with school value such as character of being proud, kind, care that developed in school. Keywords: adjective, Gusti Noeroel, characters, value.